The quest for fungal strains and their co-culture potential to improve enzymatic degradation of Chinese distillers' grain and other agricultural wastes. (October 2019) - Ming, Chunyan; Dilokpimol, Adiphol; Zou, Chenggang; Liao, Wanqing; Zhao, Liang; Wang, Meizhu; de Vries, Ronald P.; Kang, Yingqian
Abstract: Distillers' grain (DG) is one of the lignocellulosic agricultural waste streams having a high potential for biofuel production, however it is causing health and environmental problems in Southwest region of China because of improper treatment before being used for landfill. Here, we aimed to identify fungal strains that efficiently hydrolyze DG and explored the possibility to further improve the hydrolysis of DG and other agricultural wastes by co-culturing these fungi. The tested fungal strains included 11 strains that were isolated from DG (Maotai Town, Guizhou, China) and 19 strains that were selected from the CBS collection of Westerdijk Fungal Biodiversity Institute. Aspergillus niger CBS 110.42 and CBS 554.65 and Phanerochaete chrysosporium CBS 246.84 showed overall best cellulose and xylan degrading activity, whereas high laccase and peroxidase activities were detected for Oidiodendron echinulatum CBS 113.65 and Bjerkandera adusta CBS 143380, respectively. Furthermore, A. niger CBS 554.65 co-cultured with Trichoderma reesei CBS 383.78 and A. niger CBS 110.42 with P. chrysosporium CBS 246.84 showed the best improvement (up to 2- and 3-fold higher of β-glucosidase and β-xylosidase activities). These fungi and the combinations have strong potential to be further developed for local bioenergy production. Graphical abstract: Image 1 Highlights: Fungi with high (hemi-)cellulolytic activity were isolated from distiller's grain. Fungi with high ligninolytic activity were isolated from distiller's grain. CuSO4 improved ligninolytic activity of the ligninolytic strains. The best co-cultures doubled the cellulolytic and xylanolytic activities. Aspergillus niger is the appropriate choice for current industrial saccharification.